2015
DOI: 10.1016/j.humov.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Exercise can improve physical self perceptions in adolescents with low motor competence

Abstract: Adolescents with low motor competence have diminished perceptions of their physical self and tend to avoid physical activities. This study examined the outcomes of an exercise intervention that focused on improving aerobic fitness, strength, and self-perceptions in the physical domain in adolescents with poor motor coordination. The sample included 35 adolescents with low motor competence, comprising boys (n = 25) and girls (n = 10) ranging in age from 13 to 17 years, who attended two sessions per week in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 47 publications
0
18
0
3
Order By: Relevance
“…In one intervention study, McIntyre et al . () found that improving motor skills resulted in improved perceived physical competence in an adolescent sample. Similar interventions could consider targeting a younger population and should also include internalizing problems as an additional outcome measure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In one intervention study, McIntyre et al . () found that improving motor skills resulted in improved perceived physical competence in an adolescent sample. Similar interventions could consider targeting a younger population and should also include internalizing problems as an additional outcome measure.…”
Section: Discussionmentioning
confidence: 96%
“…Although perceived self‐competence may also comprise other areas, physical competence and cognitive competence are most relevant to the interference in activities of daily living and academic performance that are diagnostic requirements of DCD (American Psychiatric Association, , p74). Individuals with DCD perceive themselves as less competent physically when compared to their typically developing peers (McIntyre, Chivers, Larkin, Rose, & Hands, ; Miyahara & Piek, ). In addition, they experience greater academic difficulties and perceive themselves as having lower cognitive competence (Alloway, ; Dewey, Kaplan, Crawford, & Wilson, ; Engel‐Yeger & Hanna Kasis, ).…”
Section: Introductionmentioning
confidence: 99%
“…While personal resources include conceptions of mastery, self-esteem and social competence, social resources basically represent the social support provided by peers or parents. Concerning personal resources, recent intervention studies provide evidence that improving motor skills and participation has a positive impact on children's prosocial behavior (Piek et al, 2015) and that exercising in adolescents with low motor competencies fosters their physical self-perception (McIntyre et al, 2014). Concerning potential buffering effects, it is important to note that both resources are assumed to either mediate or moderate the risk factor-distress relation.…”
Section: Introductionmentioning
confidence: 99%
“…Children with poor motor skills often experience negative and disparaging reactions of their peers. Peers often denigrate, isolate, and stigmatize affected children because of their visible dysfunction and tease, ridicule and bully them (Losse et al, 2008;Cairney et al, 2013;McIntyre et al, 2015;Tal Saban and Kirby, 2019). This might partly explain why children with poor motor skills tend to have fewer playmates, to be ignored by peers more often, and to spend more time alone or watching others as they play (Schoemaker and Kalverboer, 1994;Smyth and Anderson, 2000;Livesey et al, 2011;Cairney et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As emotional consequences, children with poor motor skills often struggle with the direct consequences in daily activities and with their own negative feelings about it. They report lower self-esteem and self-efficacy (Losse et al, 2008;Cairney et al, 2013;McIntyre et al, 2015;Tal Saban and Kirby, 2019) and more internalizing problems (i.e., anxious and depressive symptoms) (Cairney et al, 2013;Wagner et al, 2016;Mancini et al, 2019). Internalizing problems are particularly frequent mental health problems among children with poor motor skills (Cairney et al, 2013;Wagner et al, 2016;Mancini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%